Financial literacy, use of finance and welfare in post-apartheid South Africa - Nanziri, Lwanga Elizabeth (School of Economics, 2016)
Black South Africans historically experienced discrimination with regard to access to basic rights, including the right to financial services. This culminated in the marginalisation of economic activities for large parts of the population, and subsequent economic inequality among the population. Guided by the proposition that access to formal finance improves welfare, the post-Apartheid government embarked on an aggressive programme to rectify this situation. The Usury Act of 1968 was repealed and the Financial Sector Charter was instituted in 2003. These reforms aimed to increase access to finance for all who required it, for economic activity and/or for consumption smoothing. But access to finance may not necessarily lead to better welfare. Empirical studies show that in order for access to finance to translate into improved welfare individuals need to possess the relevant financial skills. A financially literate population can effectively participate in the formal financial sector in a manner that improves their livelihoods, with spill-overs for the broader economy. This thesis investigates whether there are significant differences in the welfare of South Africans who used formal financial services compared to those who did not, during the period 2005 - 2010. The study also investigates the distribution of financial literacy, and its role in the use of especially formal financial products in the country. Such an exercise is important, given that the country has a sophisticated financial sector akin to those in developed economies, and an equally sophisticated informal financial sector. If indeed financial skills are crucial, then a society that is averse to inequality would ensure that welfare is enhanced through acquisition of the appropriate financial knowledge for effective use of finance, making access to finance a worthwhile pro-poor policy. In this study data for the period 2005 to 2009 is used to construct a measure of financial literacy.